2020
DOI: 10.1111/aab.12658
|View full text |Cite
|
Sign up to set email alerts
|

The effects of seed priming with sodium hydrosulphide on drought tolerance of sunflower (Helianthus annuus L.) in germination and early growth

Abstract: Sunflower seeds (hybrid Luka) were primed with water (hydropriming) or sodium hydrosulphide (NaHS) solutions (0.1, 0.5, 1.0 and 1.5 mM NaHS) and subsequently dried to initial moisture content. Unprimed (control) and primed seeds were germinated in a growth chamber on paper towels moistened with water or polyethylene glycol (PEG) 6000 solutions (2.5, 5.0 and 10%), mimicking different drought stress levels. To evaluate the response of the primed seeds to drought in the germination stage, the germination energy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…The early seedling stage is an extremely crucial period of plants, and is susceptible to the adverse environments ( Wang et al, 2019 ; Ocvirk et al, 2020 ; Ren et al, 2020 ). During this period, water absorption is a determining factor and it regulates various physiological processes in the plant ( Klugl and Di Pietro, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The early seedling stage is an extremely crucial period of plants, and is susceptible to the adverse environments ( Wang et al, 2019 ; Ocvirk et al, 2020 ; Ren et al, 2020 ). During this period, water absorption is a determining factor and it regulates various physiological processes in the plant ( Klugl and Di Pietro, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Safflower plants pretreated with 0.5 mM NaHS were less affected by oxidative stress because of increased accumulation of secondary metabolites and stronger oxidative defence (Amir et al 2021). However, when sunflower seeds were primed with NaHS, this did not have a persistent impact on the antioxidative defence system during early growth under drought conditions (Ocvirk et al 2021). Batista et al (2020) reported different physiological and biochemical impacts of H 2 S, zinc sulfate and potassium phosphite on soybean plants under drought conditions.…”
Section: Drought Stressmentioning
confidence: 99%
“…However, when sunflower seeds were primed with NaHS, this did not have a persistent impact on the antioxidative defence system during early growth under drought conditions (Ocvirk et al . 2021).…”
Section: Hydrogen Sulfide‐induced Abiotic Stress Tolerancementioning
confidence: 99%
“…Effect of the seed priming on early growth and germination of the seeds of Helianthus annus L. was studied in which priming with hydrosulphide was carried out in drought conditions. it was observed that relation between the drought stress and germination of seeds, where the drought conditions were inhibited, early germination of seeds were recorded [20]. Various studies have been carried out in various parts of the world regarding impact of climate change on tree species, endangered ornamental species and tree species which signifies the importance of such studies which are related with the development of cheaper methodologies for the germination of the seeds in rapidly changing environmental conditions few examples of are reported in the following lines.…”
Section: Introductionmentioning
confidence: 99%